Severe hemorrhage in a patient with dengue hemorrhagic fever after insertion of orthodontic mini-implants. A case report - Pithon, Matheus (Brazilian Dental Science, 2020)
The objective of this paper is to report a clinical case of a patient who after installing an orthodontic mini-implant returned to the dental office seven days later with a severe hemorrhage where it was inserted. Because of the severe character of the hemorrhage, the mini-implant was removed, local compression was performed, medication to control bleeding was given and some lab tests were requested. The patient returned in 24 hours with diagnosis of dengue hemorrhagic fever (DHF). The patient was referred to the specialized hematology service where the diagnosis was confirmed. Past the critical period, a new mini-implant was inserted to continue the orthodontic treatment. It can be concluded from this account that despite the mini-implants being devices of simple installation and easy removal, it is important that the patient’s systemic conditions are optimal for their overall effectiveness. Keywords Dengue; Hemorrhage; Orthodontic Anchorage Procedures.